Prevalence and Severity of Juvenile Osteochondritis Dissecans in Patients With Juvenile Idiopathic Arthritis - Hinkle, Andrew (Orthop J Sports Med, 2021)
BACKGROUND: Juvenile idiopathic arthritis (JIA) is a heterogeneous group of chronic arthritides presenting in patients aged ≤16 years, with a prevalence of 16 to 150 per 100,000. Juvenile osteochondritis dissecans (OCD) is an idiopathic disease of articular cartilage and subchondral bone, has an onset age of 10 to 16 years, and often affects the knee, with a prevalence of 2 to 18 per 100,000. Currently, there are few studies that have evaluated the relationship between JIA and OCD. HYPOTHESIS: OCD is more prevalent in children with JIA, and when diagnosed in such patients, OCD often presents at an advanced state. STUDY DESIGN: Case series; Level of evidence, 4. METHODS: The medical records of patients with diagnoses of both JIA and OCD treated between January 2008 and March 2019 at a single children’s hospital were retrospectively reviewed. Associations between timing of diagnoses, number and types of corticosteroid treatments, category of arthritis, timing of diagnoses, and lesion stability were examined with Spearman correlation coefficients. RESULTS: A total of 2021 patients with JIA were identified, 20 of whom (19 female, 1 male) had OCD of the knee and/or talus for a prevalence of 1 in 100 or 1000 in 100,000, or approximately 50 to 500 times that of the general population. These 20 patients had a total of 28 OCD lesions: 43% (9 femur, 3 talus) were radiographically stable over time, 50% (10 femur, 2 patella, 2 talus) were unstable at initial diagnosis, and 7% (2 femur) were initially stable but progressed to unstable lesions despite drilling. Twelve patients (60%) underwent surgery: 4 (20%) with stable femoral lesions for persistent symptoms despite prolonged nonoperative treatment and 8 (40%) for treatment of their unstable lesions (femoral and patellar). Within our study design, we could identify no significant associations between lesion stability and timing of diagnoses, number of joint injections, or limb deformities, nor were there associations between timing of JIA and OCD diagnoses and category of arthritis. CONCLUSION: In our population of patients with JIA, OCD lesions were found to be 50 to 500 times more prevalent when compared with published rates in the general population and often presented at an advanced state, with instability or delayed healing requiring surgery for stabilization or resolution of symptoms.